THE ROLE OF MEDICAL EDUCATION IN COMBATING HEALTH DISPARITIES IN PAKISTAN: JPUMHS;2024:14:03,119.http://doi.org/10.46536/jpumhs/2024/14.03.543 - Safdar Ali Pervez Tunio, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
Dear Editor, I write to bring attention to the critical role that medical education could play in the eradication of health disparities in Pakistan. Health disparities affect populations from vulnerable and rural regions, driven by various factors such as socioeconomic inequities, lack of access to healthcare services, inadequate public health infrastructure, and educational gaps. Educators and healthcare professionals, as educators of the future physicians, have a role in empowering them with knowledge and skills to improve these disparities and offer healthy services without inequality.